Perceived Barriers in Accessing the Reproductive Health Care Services in Odisha - Sahoo, Madhulika; Som, Meena; Pradhan, Jalandhar (Indian Journal of Community Health, 2017)
Background: The utilization of Reproductive, Maternal, and Newborn and Child health (RMNCH) services is often influenced by the socio-cultural, financial, access, political barriers acting at the community, family and individual level. Yet, very little attention has been given, either by policy makers or researchers for minimizing their effect. Aim and objective: To examine the demand and supply side barriers in accessing the maternity services and to understand the perception on maternal healthcare services. Material & Methods: The study was carried out in four districts of Odisha state, with a well representative sample of 1194 women, who delivered a child in last 2 years. Quantitative and qualitative study design was followed to collect the data. Results: The supply side barriers such as physical access and facilities were faced by the service providers. The demand side barriers such as socio-cultural, financial and access barriers were faced by the service receivers in order to avail the services. Conclusions: In order to overcome the barriers faced by the women of Odisha it is important to improve the access to services so that they get them easily. Some of the imperative actions such as strengthening community mobilization through inter-personal communication, dialogue with the key influencers in the community as well as continuous engagement with and sensitization of the service providers